I Want Two-Level with You – On the Concept of Verbal Irony - Rikalainen, Lauri (My University, 2017)
This thesis is a review of the current views on the concept of verbal irony within the scope of linguistics, with focus on the conceptual necessity of distinguishing between two layers of meaning or “universes of discourse”. The aim of this paper is show that there exists a general agreement among most modern attempts to conceptualize verbal irony. It is argued that, beneath the different theoretical frameworks, even the two competing approaches to verbal irony (pretence theory and echoic mention theory), are conceptually very similar. Additionally, verbal irony is contrasted with related concepts and modes of communication – such as sarcasm, paradox, satire and innuendo. The first section of this paper presents the Standard Pragmatic Model of verbal irony, with emphasis on Paul Grice’s seminal work. Then, some of the key problems in Grice's program will be discussed. Following that, the paper searches for similarities in modern developments by Clift (1999), Clark (1996), Curcó (2007), Gibbs (2000b) and Haiman (1990; 1998), whose approaches, while essentially expanding on Grice (1975; 1978), are agreeable to Erving Goffman's (1974) frame analytical model of communicative interaction. The thesis shows the following: 1) The traditional view of irony as mere opposition is too simplistic. 2) On conceptual and empirical grounds irony necessarily involves two contrasting levels of meaning and action. 3) The recognition of irony requires the ability to recognize a second-order belief. 4) This product of this ability is metalinguistic awareness, and the process is metarepresentational reasoning. 5) One of irony's key elements is to indicate the speaker's detachment and to express evaluation.